Sistem distribusi dan cakupan suplementasi tablet besi ibu hamil pascabencana tsunami 2004 di Kabupaten Aceh Besar Provinsi Nanggroe Aceh Darussalam - Maryani Maryani; I Made Alit Gunawan; Siti Helmyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background: The prevalence of anemia is one of indicators applied to determine pregnant woman nutrition status. The coverage of iron supplementation is still low due to poor iron distribution. In Aceh Besar regency, the prevalence of anemia in 2003 was 18.71% and become 45.5% in 2005 (report of Rapid Nutrition Assessment in Tsunami Affected Districts in NAD, February-March 2005).Objective: The study was meant to explore the distribution system and iron supplementation coverage post tsunami in Aceh Besar regency, NAD Province.Method: This was a qualitative naturalistic study; the design was investigative exploration study, and the data was collected by indepth interview. The analysis unit was health department, primary health care and villages in Aceh Besar regency. Subjects were stakeholders and pregnant women taken by purposive sampling and showed descriptively.Result: Poor health service and unreadiness of health staff affected the stagnation of iron distribution program. The un-available of guidance book and lack of nutrition staff and midwife development become so crucial. Indeed, they could not understand their jobs description in expanding iron distribution network. Furthermore, the distribution of iron tablet was done passively of pregnant woman visiting health service place. The policy of iron distribution by health department of Aceh Besar regency post tsunami 2004 were collecting data and pregnant woman ANC service held by mid-wife using iron program. The achievement of iron supple-mentation coverage was still low, though the attitude of pregnant woman has changed.Conclusion: The stagnation of basic health service and lack of health staff empowerment affected poor iron distribution for pregnant woman.